Efficacy of plant growth regulator and food preservative against Penicillium rots of Kinnow (Citrus deliciosa Ten.) fruits (Indian Journal of Arid Horticulture, 2025)
Kinnow (Citrus deliciosa) fruits are prone to attack with various post-harvest fungal rots. Among these, Penicillium rots viz., green mould rot (P. digitatum) and blue mould rot (P. italicum) are most destructive, sharing around 40 to 50 per cent of the total post-harvest fruit decay occurred in Sriganganagar belt of Rajasthan. Studies were conducted to evaluate the efficacy of Naphthalene acetic acid (NAA) and potassium metabisulfite (KMS) against these two post-harvest rots during 2004-05 and 2005-06. The results revealed that the dipping treatment of KMS solution proved significantly superior to NAA in respect of retarding the incidence of these rots. The reduction of 57.53 and 60.58 per cent incidence was recorded in green mould rot and blue mould rot respectively in pre-inoculation treatment of KMS while 50:70 and 54.53 per cent reduction in incidence of these rots was noted in post-inoculation treatment of the same chemical in comparison to control. The disease incidence was found to increase with increasing period of incubation.
Keywords: Kinnow; post-harvest; Penicillium; rots; PGR; food preservative